2009
DOI: 10.1007/s11033-009-9735-8
|View full text |Cite
|
Sign up to set email alerts
|

Human initiation protein Orc4 prefers triple stranded DNA

Abstract: In higher eukaryotes mechanism of DNA replication origin recognition and binding by origin recognition complex (ORC) is still unknown. Origin transfer studies have shown that origin sites are genetically determined, containing functionally interchangeable modules. One of such modules from the human lamin B2 origin of replication has the ability to adopt unorthodox structure partly composed of intramolecular triplex. Sequences involved in triplex formation coincide with ORC binding sites both in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, these results do not necessarily mean that the same inhibition occurs in vivo, because the length of probes/competitors used in this study is limited. It has been reported that ORC4 has an affinity to DNA triplex (43) and that ORC6 has a TFIIB-like DNA-binding domain (44). Thus, it may be possible that the entire ORC binds simultaneously to dsDNA and RNA/ssDNA if an appropriate substrate is used.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results do not necessarily mean that the same inhibition occurs in vivo, because the length of probes/competitors used in this study is limited. It has been reported that ORC4 has an affinity to DNA triplex (43) and that ORC6 has a TFIIB-like DNA-binding domain (44). Thus, it may be possible that the entire ORC binds simultaneously to dsDNA and RNA/ssDNA if an appropriate substrate is used.…”
Section: Discussionmentioning
confidence: 99%
“…42 This has been further substantiated by immunodetection of triplex signatures in HeLa cells after siRNAs-induced suppression of RPA. 41 A range of other triplex-binding proteins have been found in human, 43 other mammals, [44][45][46] flies 47 and yeast 48,49 (see Table 1). They belong to chromatin-associating protein families such as heterogeneous ribonucleoproteins (hnRNP), cytoplasmic type III intermediate filament (IF) proteins, transcription factors (TFs), high mobility group (HMG) box proteins as well as proteins involved in the cell cycle and DNA repair.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…While the identities of several of these triplex-binding proteins are as yet unknown, for those that have been identified, many have known roles involving nucleic acids. Examples include the bacterial Tn7 protein and its role in transposon insertion 21 , yeast CDP1 and chromosome segregation 22 , Drosophila GAGA factor and transcriptional regulation 23 , human Orc4 protein and replication 24 , human XPA-RPA DNA repair complexes 25 , and murine HMG proteins and a variety of DNA-dependent processes (transcription, replication, recombination and repair) 26 . Note that identified triplex-binding proteins are not limited to those that interact with DNA.…”
Section: Triplex-binding Proteinsmentioning
confidence: 99%
“…This has been more difficult to establish for triplex-binding proteins. For example, while the human Orc4 protein plays an essential role in the initiation of replication and has been found to preferentially bind pyrimidine motif triplex DNA, overexpression of this protein has not been strongly implicated in any cancer 24,43 . Certain high mobility group proteins (e.g., HMGB1) have been reported to promote the formation of purine motif triplexes.…”
Section: Triplex-binding Proteins and Cancermentioning
confidence: 99%